Synthesis and Characterization of Molecularly Imprinted Polymers (MIPs) Using Humic Acid - Tikarahayu Putri; Muhammad Ali Zulfikar; Deana Wahyuningrum; Iwan Syahjoko Saputra (Chemistry Department, The University of Brawijaya, 2022)
MIPs was synthesized through microwave assisted organic synthesis (MAOS) method by using methyl methacrylate (MMA) as functional monomer, ethylene glycol dimethacrylate (EGDMA) as cross-linker, benzoyl peroxide (BPO) as initiator, N,N-dimethyl formamide (DMF) as porogen solvent, and (HA) as template. The MIPs was successfully synthesized according to the characterization using Fourier transform infrared (FTIR) spectroscopy, scanning electron microscope (SEM), electron dispersive spectrometer (EDS), and UV spectrophotometer. FTIR shows the other functional groups peaks in the FTIR spectra of NIPs and MIPs after leaching were appeared at the wavelength of 2955 cm-1 corresponded to stretching vibration of C-H of 1459 cm-1 and 1160.06 cm-1 corresponded to the vibration bands of CH3 and O-CH3. EDS shows the MIPs after leaching have the elemental compositions of C, O, and Si with a mass of 78.34, 21.43, and 0.23%. UV spectrum shows the MIPs and NIPs have absorbance values of 0.36 nm and 0.44 nm